Effect of reduced versus usual lipid emulsion dosing on bilirubin neurotoxicity and neurodevelopmental impairment in extremely preterm infants: study protocol for a randomized controlled trial - Lindsay F. Holzapfel; Cody Arnold; Jon E. Tyson; Steven M. Shapiro; Eric W. Reynolds; Claudia Pedroza; Emily K. Stephens; Alan Kleinfeld; Andrew H. Huber; Matthew A. Rysavy; Maria del Mar Romero Lopez; Amir M. Khan (BMC Pediatrics, 2023)
Abstract Background Bilirubin neurotoxicity (BN) occurs in premature infants at lower total serum bilirubin levels than term infants and causes neurodevelopmental impairment. Usual dose lipid infusions in preterm infants may increase free fatty acids sufficiently to cause bilirubin displacement from albumin, increasing passage of unbound bilirubin (UB) into the brain leading to BN and neurodevelopmental impairment not reliably identifiable in infancy. These risks may be influenced by whether cycled or continuous phototherapy is used to control bilirubin levels. Objective To assess differences in wave V latency measured by brainstem auditory evoked responses (BAER) at 34–36 weeks gestational age in infants born ≤ 750 g or < 27 weeks’ gestational age randomized to receive usual or reduced dose lipid emulsion (half of the usual dose) irrespective of whether cycled or continuous phototherapy is administered. Methods Pilot factorial randomized controlled trial (RCT) of lipid dosing (usual and reduced) with treatment groups balanced between cycled or continuous phototherapy assignment. Eligible infants are born at ≤ 750 g or < 27 weeks’ gestational age enrolled in the NICHD Neonatal Research Network RCT of cycled or continuous phototherapy. Infants will randomize 1:1 to reduced or usual dose lipid assignment during the first 2 weeks after birth and stratified by phototherapy assignment. Free fatty acids and UB will be measured daily using a novel probe. BAER testing will be performed at 34–36 weeks postmenstrual age or prior to discharge. Blinded neurodevelopmental assessments will be performed at 22–26 months. Intention-to-treat analyses will be performed with generalized linear mixed models with lipid dose and phototherapy assignments as random effects covariates, and assessment for interactions. Bayesian analyses will be performed as a secondary analysis. Discussion Pragmatic trials are needed to evaluate whether lipid emulsion dosing modifies the effect of phototherapy on BN. This factorial design presents a unique opportunity to evaluate both therapies and their interaction. This study aims to address basic controversial questions about the relationships between lipid administration, free fatty acids, UB, and BN. Findings suggesting a reduced lipid dose can diminish the risk of BN would support the need for a large multicenter RCT of reduced versus usual lipid dosing. Trial registration Clinical Trials.gov, NCT04584983, Registered 14 October 2020, https://clinicaltrials.gov/ct2/show/NCT04584983 Protocol version: Version 3.2 (10/5/2022).